THE ACCEPTABILITY OF THE WE PASS WITH A AS COMPREHENSIVE APPROACH IN IMPLEMENTING COMPETENCY-BASED ASSESSMENT: A PRELIMINARY STUDY ON TEACHERS’ PERCEPTION - Yoyo Suhoyo; Gandes Retno Rahayu (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: A practical approach to assist teachers of medical and health profession education in designing and implementing competency-based assessment (CBA) is needed. This study aimed to investigate the acceptability of the method we developed, namely WE PASS with A as a comprehensive approach in designing and implementing CBA system.Methods: We invited medical and health profession teachers from various institutions in Indonesia who voluntarily join 4 times national workshops of the WE PASS with A. Workshop was conducted in two days (14 hours). Eighty-three teachers have participated in this study. Six closed questions using 5 Likert scales and 2 open questions was given at the end of each workshop.Results: Most teachers agreed that WE PASS with A approach covers all necessary principles for designing comprehensive assessment, helps them to understand better step by step, provides clear guideline, and can be learnt easily. However, most of them were doubt that their institutions have applied all steps in the WE PASS with A approach and can apply this approach. Teachers like the WE PASS with A approach because the approach is comprehensive, systematic, applicable, structured, simple, understood and remembered, measurable, ideal and accountable. Giving more examples, longer time to explain, more practice, socialization, and investigating the implementation were believed can improve the approach.Conclusion: The WE PASS with A can be accepted by the teachers of medical and health profession education in Indonesia. Future study needed to investigate the feasibility, acceptability, and impact of this approach.